Role of Nano-Mineral as A Feed Additive to Enhance Animal Productivity and Quality of Animal Products - Kurnia, Frans; Suhardiman, M; Purwadaria, T; Stephani, L (Indonesian Animal Sciences Society, 2012)
A development of nanotechnology today has penetrated almost all areas of life. Utilization in improving livestock production can be done by replacing commonly used conventional mineral by nanoparticles-mineral. Application of chromium (Cr), selenium (Se), silver (Ag) and copper (Cu) nanoparticles are reported to improve livestock production. However, the potential risk of the application such as mineral deposit in the body of animal itself and to people as consumers of livestock product has to be evaluated. Nanoparticle-minerals that have smaller size are easier to penetrate the cells and it is suspected that it may give more negative risk. Analysis evaluation of nanoparticle-minerals in the animal including people are still being developed. Key words: Nanoparticle-minerals, Cr, Se, Ag, Cu